2008
DOI: 10.1111/j.1365-2796.2008.01991.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the varied use of NSAIDs explain the differences in the risk of myocardial infarction?

Abstract: Abstract. van Staa T-P, Rietbrock S, Setakis E, Leufkens HGM (Medicines and Healthcare Products Regulatory Agency, London, UK; Utrecht Institute for Pharmaceutical Sciences, Utrecht University, Utrecht, The Netherlands). Does the varied use of NSAIDs explain the differences in the risk of myocardial infarction? J Intern Med 2008; 264: 481-492.Objective. To investigate the risk of myocardial infarction (MI) with diclofenac, ibuprofen and naproxen, taking into account the exposure patterns.Design. Retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 42 publications
(51 reference statements)
4
35
0
1
Order By: Relevance
“…5,8 In many reported cases, the gastrointestinal (GI) complications related to NSAIDs use was four times higher when compared to non-users. 9,10 Furthermore, findings of the current study has also indicated that patients on medications for management of chronic underlying illness are among the frequent users of NSAIDs. Up to 22.9% of the NSAIDs users were on antihypertensive medications, even though, the figure is less than the previously reported estimate of 61%.…”
Section: Drug Utilization Pattern Of Nsaidsmentioning
confidence: 93%
“…5,8 In many reported cases, the gastrointestinal (GI) complications related to NSAIDs use was four times higher when compared to non-users. 9,10 Furthermore, findings of the current study has also indicated that patients on medications for management of chronic underlying illness are among the frequent users of NSAIDs. Up to 22.9% of the NSAIDs users were on antihypertensive medications, even though, the figure is less than the previously reported estimate of 61%.…”
Section: Drug Utilization Pattern Of Nsaidsmentioning
confidence: 93%
“…The literature about NSAIDs is often contradictory, particularly about celecoxib, where the dose may be important. Increased risk of myocardial infarction and death with celecoxib and other non-selective NSAIDs has been found in large, well-designed epidemiological studies [11,19,20] as well as under clinical trial conditions [6]. It may also be relevant that, in contrast to some other studies, our cohort population was elderly with multiple co-morbidities assessed by co-prescription surrogates: 70% had at least one cardiovascular risk factor, 23% had two and 3.03% had three or more risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…(24,25)  The substituent on the nitrogen atom which reduces basicity also reduces activity except for acetyl which is metabolically labile. (26,27) Clinical uses:…”
Section: Structure-activity Relationship (Sar)mentioning
confidence: 99%